2014
DOI: 10.1093/eurheartj/ehu111
|View full text |Cite
|
Sign up to set email alerts
|

Carbamylated low-density lipoprotein induces endothelial dysfunction

Abstract: Carbamylation of LDL induces endothelial dysfunction via LOX-1 activation and increased ROS production leading to eNOS uncoupling. This indicates a novel mechanism in the pathogenesis of atherosclerotic disease which may be pathogenic and prognostic in patients with CKD and high plasma levels of cLDL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 38 publications
0
100
0
3
Order By: Relevance
“…For example, in prior studies we showed that HCit-containing lipoproteins within the atherosclerotic lesion can be generated by MPO-catalyzed carbamylation, which endows them with multiple pro-atherogenic biological properties including increased cholesterol accumulation and foam cell formation, enhanced endothelial cell apoptosis, and induction of vascular smooth muscle cell proliferation (43). Other investigators have more recently shown that carbamylated lipoproteins can also promote endothelial dysfunction and additional proinflammatory and proatherogenic activities (75). We have also shown that within inflamed joint space fluid from subjects with rheumatoid arthritis protein-bound HCit is increased, and direct injection of HCit containing peptides into the inter-articular joint space has been shown to selectively activate T cells and induce a proinflammatory erosive arthropathy in mice (44).…”
Section: Discussionmentioning
confidence: 96%
“…For example, in prior studies we showed that HCit-containing lipoproteins within the atherosclerotic lesion can be generated by MPO-catalyzed carbamylation, which endows them with multiple pro-atherogenic biological properties including increased cholesterol accumulation and foam cell formation, enhanced endothelial cell apoptosis, and induction of vascular smooth muscle cell proliferation (43). Other investigators have more recently shown that carbamylated lipoproteins can also promote endothelial dysfunction and additional proinflammatory and proatherogenic activities (75). We have also shown that within inflamed joint space fluid from subjects with rheumatoid arthritis protein-bound HCit is increased, and direct injection of HCit containing peptides into the inter-articular joint space has been shown to selectively activate T cells and induce a proinflammatory erosive arthropathy in mice (44).…”
Section: Discussionmentioning
confidence: 96%
“…15,80 However, many molecular mechanisms have been identified which with aging or under pathological conditions (obesity, diabetes mellitus, and systemic or pulmonary hypertension) impair the production of NO by eNOS and precipitate endothelial dysfunction. Major causes include increased production of ROS (causing S-glutathionylation of eNOS and uncoupling/inactivating the enzyme), 123,124 augmented presence of oxidized-LDL (causing reduced turnover, uncoupling, and dephosphorylation of eNOS) or carbamylated-LDL, 125 activation of toll-like receptors (TLR; key components of innate immunity responses) of type 4 (TLR4; stimulated by circulating lipopolysaccharides) and the downstream NFκB pathway, 126 insulin resistance (favoring proinflammatory signaling of wingless-type family member 5a activating c-Jun NH 2 -terminal mitogenactivated PK), 127 increased expression of peptidyl prolyl cis-trans isomerase (in diabetic patients; causing isomerization of the inhibitory Ser116 of eNOS), or increased levels of plasma fatty acids (during hypertension and in obesity; promoting repalmitoylation for caveolae docking [see PostTranslational Modulation of eNOS Activity section of this article], thus favoring the inhibitory interaction of eNOS with caveolin-1). 15,98,117 Other chronic deleterious influences ).…”
Section: Reduced Protein Dimerizationmentioning
confidence: 99%
“…↓, − indicates inhibition; ↑, +, stimulation; α,β, subunits of sGC; 20-HETE, 20-hydroxyeicosatetraenoic acid; AGE, advanced glycation end-products; AT II, angiotensin II; COX, cyclooxygenase; eNOS, endothelial nitric oxide synthase; H 2 S, hydrogen sulfide; LDL, low-density lipoproteins; MLCK, myosin light-chain kinase; NOX, nicotinamide adenine dinucleotide phosphate oxidase; SNO, S-nitrosylation; and XO, xanthine oxidase. by guest on May 10, 2018 http://circres.ahajournals.org/ Downloaded from on eNOS activity are prolonged exposure of the endothelial cells to increased levels of circulating aldosterone (leading to intracellular sodium accumulation thereby interrupting endothelial calcium-dependent signaling), cortisol (downregulating estrogen production), glucose (diverting glucose metabolism to the hexosamine pathway and thus increasing endothelial levels of N-acetylglucosamine which glycosylates eNOS), abnormal HDL (in patients with coronary artery disease), [128][129][130] carbamylated-HDL 125,131 (elevated in patients with end-stage renal disease and characterized by a reduced activity of the HDL-associated antioxidant enzyme paraoxonase I, and downregulating endothelial PI3K expression), high concentrations of dietary nitrate 132 (increasing eNOS phosphorylation at Thr495 and reducing that at Ser1177), the proinflammatory adipokine lipocalin-2 (in patients with obesity), the inflammatory mediator pentraxin 3 133 (activating the NFκB pathway), or progesterone (preventing the beneficial effect of estrogens). 15 Likewise, eNOS dysfunction can be favored by the relative absence of facilitating mediators such as adiponectin, angiotensin [1][2][3][4][5][6][7] (to judge from angiotensin-converting enzyme 2 deletion experiments), or apelin.…”
Section: Reduced Protein Dimerizationmentioning
confidence: 99%
“…The production of ROS in aortic tissue was analyzed by ESR spectroscopy as described previously [16]. Briefly, aortic rings were incubated in Krebs HEPES buffer containing 25 mmol/L deferoxamine (Noxygen) and 55 mmol/L diethyldithiocarbamic acid (DETC, Noxygen) together with the spin probe 1-hydroxy-3-methoxycarbonyl-2,2,5,5-tetramethylpyrrolidine (CMH, 500 mM) for 1 h at 37 C. Afterwards, supernatants were immediately analyzed by ESR spectroscopy.…”
Section: Reactive Oxygen Species In Aortic Tissue and The Spleenmentioning
confidence: 99%